Cell Cycle in Development - Kubiak, Jacek Z.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book focuses on the intersection between cell cycle regulation and embryo development. Specific modifications of the canonical cell cycle occur throughout the whole period of development and are adapted to fulfil functions coded by the developmental program. Deciphering these adaptations is essential to comprehending how living organisms develop. The aim of this book is to review the best-known modifications and adaptations of the cell cycle during development. The first chapters cover the general problems of how the cell cycle evolves, while consecutive chapters guide readers through the plethora of such phenomena. The book closes with a description of specific changes in the cell cycle of neurons in the senescent human brain. Taken together, the chapters present a panorama of species - from worms to humans - and of developmental stages - from unfertilized oocyte to aged adult.
Keywords: Life sciences; Cytology; Developmental biology; Life Sciences; Developmental Biology; Cell Biology